AWS for System Administrators Build, Automate, and Manage Your Infrastructure on the Most Popular Cloud Platform - AWS. - Lakhera, Prashant (Packt Publishing, Limited, 2021)
Take your AWS SysOps skills to the next level by learning infrastructure automation techniques using CloudFormation, Terraform, and Boto3 Key Features Book DescriptionAmazon Web Services (AWS) is one of the most popular and efficient cloud platforms for administering and deploying your applications to make them resilient and robust. AWS for System Administrators will help you to learn several advanced cloud administration concepts for deploying, managing, and operating highly available systems on AWS. Starting with the fundamentals of identity and access management (IAM) for securing your environment, this book will gradually take you through AWS networking and monitoring tools. As you make your way through the chapters, you’ll get to grips with VPC, EC2, load balancer, Auto Scaling, RDS database, and data management. The book will also show you how to initiate AWS automated backups and store and keep track of log files. Later, you’ll work with AWS APIs and understand how to use them along with CloudFormation, Python Boto3 Script, and Terraform to automate infrastructure. By the end of this AWS book, you’ll be ready to build your two-tier startup with all the necessary infrastructure, monitoring, and logging components in place. What you will learn Adopt a security-first approach by giving users minimum access using IAM policies Build your first Amazon Elastic Compute Cloud (EC2) instance using the AWS CLI, Boto3, and Terraform Set up your datacenter in AWS Cloud using VPC Scale your application based on demand using Auto Scaling Monitor services using CloudWatch and SNS Work with centralized logs for analysis (CloudWatch Logs) Back up your data using Amazon Simple Storage Service (Amazon S3), Data Lifecycle Manager, and AWS Backup Who this book is for.